CASE GOVERNMENT OF VERBS IN POLISH: PECULIARITIES OF TEACHING TO UKRAINIAN SPEAKING STUDENTS - Dorohovych, N. O. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2019)
Issues of teaching case government of certain Polish verbs which differ from those in Ukrainian are described in the article. The list of 31 Polish verbs and their Ukrainian equivalents are analyzed. The author tries to find out factors that play an important role in forming and developing grammar competence of students in the process of teaching Polish as a foreign language. The importance of teaching Polish grammar through communicative approach is also highlighted in the article. The main attention is drawn to different types of exercises on verbal government that can be useful in removing errors and overcoming the linguistic interference by Ukrainian students learning Polish.